Competency Assessment of Health Volunteers in Recording and Reporting Community Health Status in Thailand - Jittimanee, Sirinapha; Suwankij , Jirapa (Al-Hijrah Indonesia, 2023)
Health volunteers are selected based on their community knowledge, even with limited formal education. They play crucial roles including complex and technical tasks, such as recording and reporting. The aim of this study was to compare the competency in recording and reporting among health volunteers based on their education qualifications. A cross-sectional survey was conducted at a subdistrict hospital in Thailand. Data were collected using the newly developed questionnaire from a purposive sample of health volunteers (N=70). Competency differences were assessed using non-parametric statistics between 44 volunteers with primary education and 26 with secondary education or higher. A total of 70 health volunteers were included in the analyses, yielding a participation rate of 95.9% (70 out of 73). The majority of participants were female (84.3%) and the average age was 57.5 years. Those with secondary education or higher demonstrated significantly better competency in recording and reporting community health status (p = .01). The findings emphasize the need to enhance competency among health volunteers with lower education levels. Nurses in primary care settings can provide guidance, training, and continuous support to empower health volunteers for effective performance.